Analysis of gamma-delta T cells in black South African patients with active tuberculosis - Sedick, Qanita (My University, 2014)
Mycobacterium Tuberculosis is the leading cause of morbidity and mortality due to infectious diseases worldwide. South Africa has ~20% of the world’s HIV associated Tuberculosis and has the second largest reported numbers of multidrug resistant (MDR) Tuberculosis in the world. Given the complexity of the mycobacterium and its ability to evade the immune system, there is a need for dissecting the immunological response to Tuberculosis including innate like lymphocytes such as gamma-delta T cells. Gamma-delta T cells are of particular relevance as they react to phospho-proteins of mycobacteria. Gamma-delta T cells can be divided into two subsets. Gamma-delta T cells using the Vdelta2 (VD2) segment as the variable segment in their T cell receptor and gamma-delta T cells using an alternative variable segment (non VD2 T cells). We aimed to enumerate both subsets of gamma-delta T cells in the immunological response to Tuberculosis. We collected samples from three patient populations at the Charlotte Maxeke Johannesburg Academic Hospital for comparison: HIV positive patients with no evidence of Tuberculosis disease, HIV positive patients with active pulmonary Tuberculosis and a healthy control group. We used a nine colour flow cytometric panel to enumerate the frequency of gamma-delta T cells in these participant groups. We found that the VD2 T cell subset was reduced in the HIV positive group and the dual HIV positive TB positive group compared with healthy controls, which mirrored the loss of CD4 T cells in these patients. Conversely, the non VD2 subset of gamma-delta T cells showed a statistically significant increased frequency in HIV positive patients and dual HIV positive TB positive patients compared to healthy controls. The frequency of gamma-delta T cells, expressed as a percentage of total T cells, was significantly increased in HIV positive patients and not non- significantly increased in the HIV positive TB positive groups compared to healthy controls. This skewing of the gamma-delta T cell repertoire in HIV positive patients and HIV positive patients with active Tuberculosis may have specific immune implications. The mechanism of the loss of VD2 T cells in HIV and HIV associated Tuberculosis has not been elucidated. The loss of VD2 gamma-delta T cells in HIV and HIV associated Tuberculosis may underlie susceptibility to Tuberculosis disease.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree, Master of Medicine in Haematopathology. Johannesburg, 2014
Keywords: T-Lymphocytes; Mycobacterium Tuberculosis